2018
DOI: 10.1002/acn3.582
|View full text |Cite|
|
Sign up to set email alerts
|

Whole‐exome sequencing in 20,197 persons for rare variants in Alzheimer's disease

Abstract: ObjectiveThe genetic bases of Alzheimer's disease remain uncertain. An international effort to fully articulate genetic risks and protective factors is underway with the hope of identifying potential therapeutic targets and preventive strategies. The goal here was to identify and characterize the frequency and impact of rare and ultra‐rare variants in Alzheimer's disease, using whole‐exome sequencing in 20,197 individuals.MethodsWe used a gene‐based collapsing analysis of loss‐of‐function ultra‐rare variants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 33 publications
6
99
0
Order By: Relevance
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2 , ABCA7 , SORL1 , and PSEN1 (Blue et al., ; Guerreiro et al., ; Kim, ; Patel et al., ; Raghavan et al., ). Many of the others did not seem likely to have any plausible role in AD susceptibility but there were some exceptions that we list here.…”
Section: Resultsmentioning
confidence: 99%
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2 , ABCA7 , SORL1 , and PSEN1 (Blue et al., ; Guerreiro et al., ; Kim, ; Patel et al., ; Raghavan et al., ). Many of the others did not seem likely to have any plausible role in AD susceptibility but there were some exceptions that we list here.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a rare variant in the 3′ UTR of RAB10, a member of the RAB family of small GTPases that are critical regulators of membrane trafficking and vesicular transport , confers resilience to AD 70,71 . Furthermore, coding variants that increase risk for AD have been identified in SORL1 6,72 , a member of the vacuolar protein sorting 10 (VPS10)domain-containing receptor family and the low density lipoprotein receptor (LDLR) family of APOE receptors that is expressed primarily in microglia in the brain 18 and plays important roles in the endolysosomal system and APP processing 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2, ABCA7, SORL1 and PSEN1 (Blue et al, 2018;Guerreiro et al, 2013;Kim, 2018;Patel et al, 2019;Raghavan et al, 2018). PIK3R1 codes for a key component of the PI3K/Akt/GSK-3β signalling pathway and in neuronally differentiated PC12 cells activation of this pathway is neuroprotective against Aβ25-35-induced apoptosis and tau hyperphosphorylation (Cheng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A number of analyses utilising this dataset have been published to date. One study incorporating this dataset with others identified 19 loss of function variants of SORL1 in cases as opposed to 1 in controls and a collapsing test of loss of function ultra-rare variants highlighted other genes including GRID2IP, WDR76 and GRN (Raghavan et al, 2018). A subsequent study used variant-based and gene-based tests of association and followed up significant or suggestive results in other samples to implicate three novel genes, IGHG3, AC099552.4 and ZNF655 as well as novel and predicted functional genetic variants in genes previously associated with Alzheimer's disease (AD) .…”
Section: Introductionmentioning
confidence: 99%